Virtual mobility: the new challenge for higher and continuing education institutions - Barbara Class (2012)
European universities are faced with important issues, in particular an ageing population, a decrease in the number of learners per institution, globalization and competition. At the same time, physical mobility represents one of the most successful projects of the European Union. Since physical mobility is rather demanding in financial and organizational terms, only 4% of learners from European higher education institutions can benefit from the programme today. The objective of the European Commission is to reach 20% in 2020 (European Commission, 2011a), but even with an increase of 16%, a minority of learners will be concerned. In parallel, employers promote stays abroad during studies. Erasmus programmes are offered only to BA/MA/PhD students and not to Continuing Education learners, but in a lifelong learning (LLL) perspective, mobility should also be available to adult and senior learners. As a matter of fact, European higher education and continuing education institutions have to reinvent their offers, taking into account the paradigm of an ageing population and the need for professional reconversions or specialisations. The case of the University of Genevas continuing education courses is discussed with a majority offered in a face-to-face format in terms of the age of the different audiences and their motivation for following a continuing education course. Starting from there we move to the European context in terms of LLL and virtual mobility. In accordance with the literature, we define virtual mobility in reference to physical mobility. In the rest of the paper we discuss concrete frameworks that could support the development of virtual mobility. Scenarios, taken from the VIRQUAL - Virtual Mobility and European Qualification Framework European project (VIRQUAL website, 2010), show how it could all work and fit together, across countries, across generations and across contexts. Finally we discuss the different European projects dealing with virtual mobility and the perspectives researched.